COVID-19 & informal settlements: is 'Stay Home' safe?. Issue 4 (29th July 2022) - Nix, Emily; Paulose, Jacob; Lakhanpaul, Monica; Factor-Litvak, Pam; Parikh, Priti; Altamirano-Medina, Hector; Bou Karim, Yasmin; Manikam, Logan; ,
Abstract : The disproportional burden of coronavirus (COVID-19) and vulnerability to containment measures in informal settlements have been recognised; however, the role of poor housing conditions in propagating these remains neglected. Poor housing conditions makes it difficult to effectively implement social distancing measures. With increased time spent in cramped, dark and uncomfortable indoor environments, water and sanitation outside the home, and no outdoor space, higher exposure to existing health hazards and high levels of stress, with women and children being most vulnerable, are anticipated. Through this commentary paper, we reflect on these interconnections and recommend immediate measures and the long-term need for adequate housing for health and well-being.